2022
DOI: 10.3390/toxics10090520
|View full text |Cite
|
Sign up to set email alerts
|

Human Health Risks and Air Quality Changes Following Restrictions for the Control of the COVID-19 Pandemic in Thailand

Abstract: The coronavirus (COVID-19) pandemic first impacted Thailand in early 2020. The government imposed lockdown measures from April to May 2020 to control the spread of infection. Daily lifestyles then morphed into a so-called new normal in which activities were conducted at home and people avoided congregation in order to prevent the spread of an infectious disease. This study evaluated the long-term air quality improvement which resulted from the restrictions enforced on normal human activities in Thailand. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(39 reference statements)
0
5
0
Order By: Relevance
“… Mahato et al (2020) , Sharma et al (2020) , and Naqvi et al (2021) have observed that the lockdown improved the air quality in India by 31–54%, 15–44%, and 17.75–20.70%, respectively. Compared to non-lockdown periods, the national or city-scale air quality improvement for Thailand ( Kaewrat et al, 2022 ), Korea ( Seo et al, 2020 ), and Iran ( Yazdani et al, 2021 ) was approximately 30%, 44.8–48.7%, and 8%, respectively. In China, national-level studies have revealed that the air quality index (AQI) reduced by approximately 5 (367 cities; Ming et al, 2020 ), 20.56 (326 cities; Song et al, 2021 ), and 19.84 points (1605 air quality monitoring stations covering all of the prefectural cities; He et al, 2020) during epidemic prevention and control periods.…”
Section: Introductionmentioning
confidence: 99%
“… Mahato et al (2020) , Sharma et al (2020) , and Naqvi et al (2021) have observed that the lockdown improved the air quality in India by 31–54%, 15–44%, and 17.75–20.70%, respectively. Compared to non-lockdown periods, the national or city-scale air quality improvement for Thailand ( Kaewrat et al, 2022 ), Korea ( Seo et al, 2020 ), and Iran ( Yazdani et al, 2021 ) was approximately 30%, 44.8–48.7%, and 8%, respectively. In China, national-level studies have revealed that the air quality index (AQI) reduced by approximately 5 (367 cities; Ming et al, 2020 ), 20.56 (326 cities; Song et al, 2021 ), and 19.84 points (1605 air quality monitoring stations covering all of the prefectural cities; He et al, 2020) during epidemic prevention and control periods.…”
Section: Introductionmentioning
confidence: 99%
“…According to a research by (Kaewrat et al, 2022;Leelawat et al, 2022), operating enterprises in the Pathaya tourism sector was a significant difficulty since owners had to negotiate a challenging and ever-changing environment. Many operating challenges, such as high expenses, fierce rivalry, and erratic demand, plagued the proprietors.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has had a big effect on the tourism business in Thailand. The decline in international tourism, the bad news in the media, and the change in consumer behaviour have all led to a big drop in the industry's revenue and profits (Kaewrat et al, 2022;Leelawat et al, 2022). As the pandemic continues to evolve, it is essential for the hospitality industry in Thailand to adapt and find ways to mitigate the impact of the pandemic (Hyder et al, 2023).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…On 30 January 2020, the WHO Emergency Committee designated COVID-19 as a global health emergency; as of 12 August 2022, COVID-19 had caused at least 585,950,085 confirmed cases and 6,425,422 deaths globally (WHO). The COVID-19 epidemic has had an unprecedented influence on global air pollution [ 18 , 19 , 20 , 21 , 22 , 23 ]. The abrupt COVID-19 pandemic offers a chance to research the impact of urban blockade policies on the change of air pollutants, and to describe the normal modes of air pollution under the disappearance of the epidemic [ 24 ].…”
Section: Introductionmentioning
confidence: 99%